Evidence for homologous recombination in Chikungunya Virus - Casal, Pablo E. (2015)
Chikungunya Virus (CHIKV), a mosquito-transmitted alphavirus, causes acute fever and joint pain in humans. Recently, endemic CHIKV infection outbreaks have jeopardized public health in wider geographical regions. Here, we analyze the phylogenetic associations of CHIKV and explore the potential recombination events on 152 genomic isolates deposited in GenBank database. The CHIKV genotypes [West African, Asian, East/Central/South African (ECSA)], and a clear division of ECSA clade into three sub-groups (I-II-III), were defined by Bayesian analysis; similar results were obtained using E1 gene sequences. A nucleotide identity-based approach is provided to facilitate CHIKV classification within ECSA clade. Using seven methods to detect recombination, we found a statistically significant event (p-values range: 1.14×10-7-4.45×10-24) located within the nsP3 coding region. This finding was further confirmed by phylogenetic networks (PHI Test, p=0.004) and phylogenetic tree incongruence analysis. The recombinant strain, KJ679578/India/2011 (ECSA III), derives from viruses of ECSA III and ECSA I. Our study demonstrates that recombination is an additional mechanism of genetic diversity in CHIKV that might assist in the cross-species transmission process.